UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS V MATA PELAJARAN IPA MATERI EKOSISTEM DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING - Dwi Purnomo; Zuchrotus Salamah (Universitas Ahmad Dahlan, 2019)
This research is based on the problem of the low student learning outcomes in science learning at Muhammadiyah Elementary School Klepu, Sleman Regency. The teacher still uses a conventional learning model so that the learning atmosphere becomes rigid and ultimately makes student learning outcomes lower. Therefore the teacher seeks to use the Discovery Learning learning model to create an interesting and enjoyable learning atmosphere. This study aims to improve learning outcomes of science through the Discovery Learning learning model in fifth grade students of SD Muhammadiyah Klepu Sleman Regency Academic Year 2018/2019. This type of research is classroom action research. This research was conducted in 2 cycles. This research was conducted on fifth grade students of SD Muhammadiyah Klepu Sleman Regency. Data was collected using observation sheets and test questions. The data analysis technique in this study is descriptive analysis. The results of this study indicate that learning through the Discovery Learning learning model can improve student science learning outcomes. The average value of post-test Cycle I is 62.2 and the percentage of mastery learning is 9.5%. In the second cycle the average score of the post-test increased to 80.91 and the percentage of mastery learning was 76.2%. Based on data obtained from the study, it can be concluded that learning through the Discovery Learning learning model can improve student learning outcomes.